Logistics Controlling: The Driver of Advanced Logistics Efficiency (Global Journal of Management and Business Research, 2017)
Logistics controlling is an indispensable element of success for companies in advanced economies. The complex nature of the economic and logistic processes requires that they are being monitored and kept under control so they are properly coordinated, modified and adjusted when needed. Logistics controlling is a technology that is designed to satisfy these requirements. Success and efficiency in business largely depends on how accurately the companies are able to delineate their own profiles and environments, and how flexible they are in adjusting themselves to the changes going on in their environment. In my research I aspire to prove that logistics controlling is a potent tool for companies desiring to be more successful in business by improving their productivity.
Keywords: logistics; information; readiness; management; control